Social Networking As An Awareness Mechanism To Develop Mothers’ Family Awareness To Protect Children From The Dangers Of Pedophilia - A Socio-Communicative Family Vision - Imane Hamri, Mohammed Elhadi Kaci; Taieb Djaballah, Djazia Redaouia; Amina Agrane (Journal of Informatics Education and Research, 2025)
Amidst this accelerating technological momentum, social media is no longer a recreational or temporary option. Rather, it has become an inevitability imposed by the nature of the digital age, forming an important part of our lives, including our family life. It has come to play a vital role in shaping and guiding family awareness, significantly impacting how family members interact and communicate, and even how they deal with broader societal issues and the risks they pose to individuals and children in particular. Recently, the phenomenon of child sexual exploitation has become a major concern that threatens the security and psychological stability of the child on the one hand, and the family on the other. This prompted us to shed light on this phenomenon within a research context and through a socio-communication diagnosis. This scientific treatment focused on the role and effectiveness of social media and its contribution to enhancing family awareness among mothers to protect and immunize children and confront the threat of sexual exploitation and pedophiles. This is achieved through awareness campaigns that make parents more careful to raise a child who is more aware of the dangers and more keen to protect them. Same.